Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1399202 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Arthropoda" ] } The dataset includes 1399202 records from 17594 constituent datasets: 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 134 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 3496 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 23 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 193 records from A Compendium Of Distributional Records For Oroperla Barbara Needham, 1933 (Plecoptera: Perlodidae), With Additional Documentation Of Reproductive Morphology And Biology. 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 5 records from New species of Isometopinae (Hemiptera: Miridae) from the Ivory Coast and Yemen. 3 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 18 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 265 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 1 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 3 records from A new Vaejovis from the Mogollon Highlands of northern Arizona (Scorpiones: Vaejovidae). 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 4 records from Notes on two species of the genus Atemnus Canestrini (Pseudoscorpiones: Atemnidae) from China. 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1905 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 16 records from Observations du Conservatoire botanique national du Bassin parisien.. 8 records from Steinbruch Mainz-Weisenau, 4.Jahr. 12858 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 4 records from Rediscovery of Lustrina Kurian (Hymenoptera, Chrysididae), with redescription of L. assamensis Kurian. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 57 records from Manx Wildlife Trust - Records. 17619 records from Tasmanian Natural Values Atlas. 10380 records from Macaulay Library Audio and Video Collection. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2318 records from Museu Darder de Banyoles. 3764 records from Swiss National Cicadidae Databank. 3 records from A new species of Microdaccus SCHAUM 1864 from Cyprus (Coleoptera, Carabidae, Lebiini). 7 records from Ovilyra, a new genus of leucosiid crab (Crustacea: Decapoda: Brachyura) from the West Pacific. 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 9 records from A giant nektobenthic radiodont from the Burgess Shale and the significance of hurdiid carapace diversity. 17109 records from Lepidopterous specimens of Yamagata Prefectural Museum. 652 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 4 records from Two new sympatric species of Eusarsiella (Ostracoda: Myodocopida: Sarsiellidae) from the Florida Keys with a morphological phylogeny of Sarsiellinae. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 16 records from A new species of Neoliomera Odhner, 1925, from the western Pacific, and the first record of N. demani Forest & Guinot, 1961, from Taiwan (Crustacea: Decapoda: Brachyura: Xanthidae). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1295 records from Study on plankton at the port of Ostend in 1965. 103 records from Priest Pot species list, Cumbria, Britain. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 5 records from Ostracods (Crustacea) associated with microbialites across the Permian-Triassic boundary in Dajiang (Guizhou Province, South China). 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1990 records from Orthoptera - SMF. 5709 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 1 records from Redescription of Echinoplax rubida Alcock, 1895, a valid species of Pleistacantha from the Andaman Sea (Crustacea: Brachyura: Oregoniidae). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 29 records from Four new species of the subgenus Tachycines (Gymnaeta) (Rhaphidophoridae Aemodogryllinae: Aemodogryllini) from caves in northern Guizhou, China. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 41 records from Systematics, phylogeny and biogeography of genus Balkanopetalum Verhoeff, 1926 (Diplopoda: Callipodida: Schizopetalidae). 3 records from University of Michigan Museum of Paleontology - Vertebrates. 1 records from Contribution to the knowledge of oribatid mites of the genus Austrocarabodes (Acari, Oribatida, Carabodidae) of Madagascar. 42 records from Morphological and molecular analyses support the amphi-Atlantic distribution and taxonomic status of the snapping shrimp Alpheus intrinsecus Spence Bate, 1888 (Crustacea: Decapoda: Alpheidae). 100 records from Données naturalistes d'Océane ROQUINARC'H. 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 672 records from Colección de Entomología - Curculionidae. 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 81 records from Flora y Fauna asociada a servicios ecosistémicos de polinización y zoocoria para 10 remanentes de bosque seco tropical en el Valle del Cauca. 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 1 records from Anteon hubeni a new species from Ecuador (Hymenoptera: Dryinidae). 940 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 7 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 2 records from Perscheloribates Paratzitzikamaensis N. Sp., With Supplementary Descriptions Of Scheloribates Elegans And Monoschelobates Parvus (Acari, Oribatida, Scheloribatidae) From Ecuador. 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 5886134 records from International Barcode of Life project (iBOL). 2969 records from Carabidae of Mordovia State Nature Reserve. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 29 records from LBV 100 - Artenvielfalt am Rothsee. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 7 records from Megaluropidae *. 109 records from Données naturalistes de Xavier BONNET. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 17579 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 60 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 6237 records from Plecoptera. 4 records from Flora und Fauna in unserer Kita. 2 records from Two new species of the genus Awas from Central and East China (Coleoptera: Staphylinidae: Pselaphinae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 15337 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 41 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 22 records from First record of the subfamily Brachycyrtinae (Hymenoptera, Ichneumonidae) from continental Africa, with description of three new species. 2 records from Two new aphid species of the genus Cryptomyzus Oestlund, 1922 (Hemiptera Aphididae) from Kazakhstan, and keys to apterous and alate viviparous females. 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 3 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 15 records from Some finds of flora and fauna in Kharkiv region. 1 records from Discovery of the bee genus Perdita in the West Indies (Hymenoptera: Andrenidae): a new species from Isla Cabritos in the Dominican Republic. 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 47 records from Artenvielfalt auf dem Schulgelände. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 5 records from New data on the oriental Xantholinini. 36. Description of the male of Thyreocephalus elegantissimus BORDONI, 2012 and new records (Coleoptera, Staphylinidae) 253 ° contribution to the knowledge of the Staphylinidae. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 6848 records from National Museum of Natural Science. 23 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from Collection Francaise de Bacteries Phytopathogenes. 16 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 27 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 79 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 36 records from Données de la naturaliste Laurence Beauchamp. 1614 records from New Brunswick Museum Collection. 123 records from Ladybirds of Ireland. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 13545 records from Données naturalistes de Bruno OGER. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 6 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 1 records from Norwegian Lepidoptera working group. 11 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 16 records from Données naturalistes de ROLLAND Blandine. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 436 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 10 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 55 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 32 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 13 records from Anmerkungen zur Gattung Dapsa L, 1829 (Coleoptera, Endomychidae). 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 125705 records from Paleobiology Database. 3 records from Distribution Of Moselia Infuscata (Claassen, 1923) (Plecoptera: Leuctridae) In Canada. 3509 records from Entocytheridae (Ostracoda) World Database. 26 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 11 records from Changes in the genus Beana Walker (Beaninae Zahiri & Holloway) with two new species and removing Beana nitida Tams to a new genus Beanoides (gen. nov.). 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 7 records from Thomas L. Casey and Rhode Island. 151 records from A checklist of the non-leaf-cutting fungus-growing ants (Hymenoptera, Formicidae) from Colombia, with new biogeographic records. 3 records from Sächsische Schweiz (Pfaffenstein). 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 26 records from Some lesser known silent crickets (Orthoptera: Gryllidae: Euscyrtinae) from the hilly tracts of India. 4298 records from ColRest_Raw1. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 567 records from database_fish_estuary_boso. 3 records from A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 2 records from Two new species and ten new records of Heteroptera from Turkey, including the first record of the potential alien Campylomma miyamotoi in the Western Palaearctic. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 215 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 4 records from Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 870 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1743 records from Updating the knowledge of the flower flies (Diptera: Syrphidae) from Chile: Illustrated catalog, extinction risk and biological notes. 106211 records from flora&fauna(NIBR)2019. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 17 records from Roter Berg Werdau (Leubnitz). 1201 records from Hormigas (Hymenoptera: Formicidae) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 218 records from Cryptobiont assemblages's dataset of coral reefs using ARMS in B10 Reef and Mahahual Reef of the Great Caribbean. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3258 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 3 records from New genera of Alleculinae (Coleoptera: Tenebrionidae: Alleculinae: Alleculini) from the Oriental Region. Part XI-Vietnalia gen. nov.. 4 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 6 records from Pollen and spore abundance of Hole 42-380A. 3952 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 5 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 80 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 1 records from A new species of the genus Protoplotina Miyatake (Coleoptera: Coccinellidae) from India. 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 2 records from Analyses of the recent components of sediment core PS1277-1. 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 1 records from Redescription of the remarkable Zhiltzovaia amabilis (Jewett, 1958) comb. nov. (Plecoptera, Perlodidae) based on types and new material from Himalaya and Pamir Mountain systems. 8275 records from MfN - Mallophaga Collection. 18 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 69 records from The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records. 18 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 5 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 77 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 31478 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 32 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 5418 records from Données des membres de l'Association française d'Arachnologie. 16 records from Artenvielfalt des "Grünen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 66 records from Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym?. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 32 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 8 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 22008 records from OPIE_National_2017_12_18. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 4854 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 14 records from An annotated checklist of Ciidae (Coleoptera: Tenebrionoidea) of Iran. 3 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 92 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 73 records from Notes On Some Fulgoroidea Of Guam. 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 20 records from Two Hexapleomera species from Japan, with a new species description and discussion of phylogenetic relationships within Hexapleomera (Crustacea: Tanaidacea). 382 records from orthopteracollections-nhmj-ioj. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 17 records from Notes On Claudioperla Tigrina (Klapálek) In Ecuador (Plecoptera: Gripopterygidae). 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 115 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 119 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 466 records from Collections of Bioclass, school #179, Moscow. 506 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 216 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 718 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 282 records from Middlebury College Bee Collection. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 135 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 11983 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 3 records from Two new species of flavomaculata-group of the genus Macrophya Dahlbom (Hymenoptera: Tenthredinidae) from China. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 44 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 25 records from Novas Espécies De Acrosternum Subgênero Chinavia (Heteroptera, Pentatomidae, Pentatomini). 1 records from Nothrus pulverulentus. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Benthic macrofauna abundance of sediment core 12930-063. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 19 records from Pollen analysis of sediment profile TR0 from Truennensee. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 10 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 37 records from Überall ist Wunderland. 162 records from INNS Data: All Taxa (West Wales). 445 records from Macrobenthos Chukchi Sea, 1986. 2802 records from The Taiwan Roadkill Observation Network Data Set.. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 83 records from Données naturalistes de Ingénieurs écologues GEREA. 2 records from Groehnaltica batophiloides, a new genus and species of flea-beetles (Coleoptera Chrysomelidae) from Baltic amber, described using X-ray microtomography. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 4 records from sediment metagenome Metagenome. 1 records from Taxonomy of the weevil genus Plumolepilius Barrios-Izás & Anderson (Coleoptera Curculionidae: Molytinae: Conotrachelini): new species from Central America. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 27 records from The Nymph Of Holcoperla Angularis (Wisely) (Plecoptera: Gripopterygidae) From New Zealand. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 50 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 149 records from Données naturalistes de Marie-France LECCIA. 5 records from Faunal assemblage of sediment core TR149-31. 17 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 18 records from Naturtag. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Department of Plant Protection. 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 29858 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 2227 records from IRAD Cameroon insect collection. 52 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 169 records from Sistema de Monitoreo de Arrecifes Coralinos - SIMAC: Abundancia de invertebrados vágiles. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 626 records from Etude des coléoptères de l'ENS de Voulangis (77). 2 records from Neue Milbenarten aus Kärnten. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2818 records from Grand_Site_Sainte-Victoire_2017_12_18. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 32 records from Revision of the genus Tityopsis Armas 1974 (Scorpiones Buthidae) Part 1 General updates and description of four new species. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 65 records from Synopsis of Lestes from Brazil with description of Lestes demarcoi sp. nov (Zygoptera: Lestidae). 13 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 3 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 74847 records from Entomology Collection at the Natural History Museum of Utah. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 40 records from makran-chabahar-arthropods. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 125 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 10 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 142 records from Hartland Nature Club Lepidoptera Collection. 404 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 36 records from Type specimens of Ichneumonidae (Hymenoptera) described by Brèthes held in the Museo Argentino de Ciencias Naturales “ Bernardino Rivadavia ”, Argentina. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 29 records from UTEP Invertebrates (Arctos). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4 records from Taxonomy of the Myrmicine ant genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in the Arabian Peninsula. 24 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 1 records from The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 20 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 84 records from Données espèces - Expertise IQE 306. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 1529 records from Données Nature 18 - Études faune 2016. 15 records from Insect Collections of Okomu National Park- Nigeria. 237602 records from University of Minnesota Insect Collection. 291402 records from ARABEL - Arachnologia Belgica. 177 records from Heinersdorfer Sumpfwiese. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 45 records from A taxonomic revision of the genus Hexarhopalus (Coleoptera, Tenebrionidae Cnodalonini) from China. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 3 records from The family Opilioacaridae (Acari: Parasitiformes) in Argentina, with description of two new species. 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 2 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 419 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 348 records from Antarctic pycnogonids. 14 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 2 records from Malgacheliodes martensi spec. nov. (Acari, Oribatida, Licnodamaeidae) from South Africa. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from Naturschutzgebiet Müchelholz (Mücheln). 140 records from Algae of the Recherche Archipelago , Western Australia (2002-2003). 24 records from Wiese am Waldrand (Gurtweil). 15 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1 records from A new species of cave inhabiting Scotoleon Banks from Baja California (Neuroptera: Myrmeleontidae: Brachynemurini). 2 records from A new species of the subgenus Duolandrevus (Eulandrevus) Kirby, 1906 from Guangxi, China (Orthoptera: Gryllidae: Landrevinae). 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 23 records from Liether Park (LMS), 5a. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 4152 records from Midden-Limburg Fish Ponds Survey. 5 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from Culicidae of Guam. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 8 records from Two new species of Psyttalia Walker (Hymenoptera, Braconidae, Opiinae) reared from fruit-infesting tephritid (Diptera) hosts in Kenya. 1 records from Zetes ephippiatus. 369 records from National System of Protected Areas in Poland - Animals. 2 records from Leiner-Herbar Konstanz. 13 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 8 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 130 records from Kyklades-data of the Central Aegean Sea. 8956 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 895 records from Geometridae de France métropolitaine. 105 records from bmhs_moth_collection. 144 records from Cactophilic Drosophila and Opuntia. 20 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 5 records from A ghost in the salt: A new species of halotolerant tube-web spider in the genus Ariadna (Araneae: Segestriidae). 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4193 records from Leicestershire and Rutland Aculeate Records. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 9 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 38 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 2 records from Primagistemus gen. nov. (Acari: Prostigmata: Stigmaeidae). 16618 records from Suivi Temporel des Libellules (STELI). 1 records from The larvae of Chinese Hydropsychidae (Insecta: Trichoptera), Part III: Hydromanicus melli Complex, H. canaliculatus, and H. umbonatus. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 11 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 13 records from Ichneumonid wasps from Madagascar. VI. The genus Pristomerus (Hymenoptera: Ichneumonidae: Cremastinae). 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 11 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 54786 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1 records from A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species. 97 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 1 records from Distributional notes on some Nosodendridae (Insecta, Coleoptera) - XXI. A new Nosodendron species from Malaysia. 25471 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 985 records from Bees in the UVM Zadock Thompson Zoological Collection. 5 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 22 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 8306 records from Données naturalistes de Benoit MARTHA. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 25393 records from Observations occasionnelles Parc national des Pyrénées. 6 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 265 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 20 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 21 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 316 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 51 records from Diversity of beetles associated with watermelon crops Citrullus lanatus (Thunb.) Mats. in the region of Ouargla (southern Algeria). 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 4 records from Description of new genus and species of Ochlerini from Central America (Hemiptera: Pentatomidae: Discocephalinae) ¹. 24 records from The geometrid moths of Ethiopia I: tribes Pseudoterpnini and Comibaenini (Lepidoptera: Geometridae, Geometrinae). 259 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 112 records from Antarctic Pycnogonids II. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 10149 records from Bumblebees, cuckoobees and butterflies in southern Poland. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 5424 records from 2020_biodiversity_information_specimen. 149 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1144 records from Données naturalistes de Quentin ROME. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 269 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 20 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 749 records from Carabidae of Wales and England. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 8259 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 77 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 857 records from DFO Zoobenthos data from upper Frobisher Bay, 1967 to 1973. 12 records from Two new species of Rhiginia Stål, 1859, with taxonomical notes on species in the “ cruciata-group ” of this genus and an updated key to the New World genera of Ectrichodiinae (Heteroptera, Reduviidae). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 8 records from Complementary description of Podocinella misella (Berlese, 1913) (Acari: Podocinidae) and a key to world species of the genus. 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 1290 records from Diversity of Spiders from Azorean Trails. 70 records from Ensemble des données Orthoptères. 2 records from Chauliodites niedzwiedzkii sp. n. (Grylloblattida: Chaulioditidae) from Triassic sediments of Poland. 2185 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 5 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 4 records from A new species of the genus Cyrtonion (Coleoptera: Hydrophilidae: Megasternini) from the Democratic Republic of the Congo. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 9151 records from NEON Biorepository Carabid Collection (DNA Extracts). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 24 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 28 records from Données naturalistes de Franck MERLIER. 28 records from US herbarium - Smithsonian Institute - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1 records from Natura 2000 Vallée de la Seille. 2678 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 174 records from Etude naturaliste des landes et pelouses à Fulchiron, Maisse (91). 9 records from New species of the cicada genus Semia Matsumura (Hemiptera: Cicadidae) from China and a phylogeny of Semia spp. and their relatives based on molecular data. 140 records from MfN - Fossil Fish Collection. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 1070 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 47334 records from NOAA AFSC North Pacific Groundfish Observer. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 191 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 129 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 1308 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 447 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 52609 records from Insects, Outer Hebrides. 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 43 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 18 records from An der Ohm, (Wettsaasen). 5 records from Isoptera of Guam. 185 records from Inventaire des odonates d'intérêt communautaire. 65 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 2112 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 25 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8177 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from Weeds Australia. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 55 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 14 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 1 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 6 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 137 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 46 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 20 records from Naturgrundstück (Eutin). 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 229 records from données araneologiques de LEENKNEGT Virginie. 3 records from Zoology in the Middle East. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 22083 records from Données de l'Observatoire de la Faune de Bourgogne. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 1 records from Developmental Biology among Corbiculate Bees: Bombus impatiens, Including Observations on Its Egg Eclosion. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 21 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 1 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 3 records from Analyses of the recent components of sediment core PS1011-1. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 6598 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 5 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 103 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 7 records from New Species Of Tyloperla (Plecoptera: Perlidae) From Vietnam And Thailand. 1036 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 238 records from Données naturalistes d'Olivier LAURENT. 13 records from Coleção de Coleoptera da Universidade de Brasília. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from Phliantidae *. 115 records from Fermanagh Flora. 2324 records from Eriophyoid Mites of Poland. 9 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 45 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 6 records from First record of the genus Microtityus Kjellesvig-Waering, 1966, from Puerto Rico, with description of two new species (Scorpiones: Buthidae). 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 101 records from STERF 2014/2015 Hasparren (64) par l'association EcoGIS. 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 1037 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 549 records from Données du naturaliste Julien Birard provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from Additional Characters In Perlesta Baumanni Stark (Plecoptera: Perlidae), With Notes On Other Ouachita Mountain Species. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 5 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 827 records from Museu_Paraense_Emilio_Goeldi_Microfosseis_Collection. 10 records from Bees of the family Halictidae Thomson, 1869 from Dominica, Lesser Antilles (Hymenoptera: Apoidea). 14 records from Streuobstwiese Stedar 2009. 1 records from On the Chilopoda from Turkey. 4 records from Proposal of Marbefia, gen. n. and Inermiphonte, gen. n., including updated keys to the species of Pseudonychocamptus Lang, 1944 and Paralaophonte Lang, 1948 (Copepoda, Harpacticoida, Laophontidae). 145 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservación Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 8 records from Taxonomy of the genus Cyrtopholis Simon, 1892 (Araneae, Mygalomorphae, Theraphosidae): Cuban species described by Pelegrín Franganillo Balboa. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 6 records from New Species of Neotibilis Grazia & Barcellos (Hemiptera: Pentatomidae: Pentatomini). 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 8 records from CM Vertebrate Paleontology Collection. 3 records from Die Bachspezies 2008/2009. 38 records from Description of the male of Cybaeodamus lycosoides (Nicolet), with new distributional data for C. meridionalis Lise, Ott & Rodrigues (Araneae, Zodariidae). 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 22 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 81 records from Diura Washingtoniana (Hanson) Resurrected From Synonymy With D. Nanseni (Kempny) (Plecoptera: Perlodidae), Supplemented With A Description Of The Larva And Egg And Comparison To Other Congeners. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 14033 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 26 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 2 records from Abundance of benthos infauna at station GIK23042-2. 4 records from Streuobstwiese. 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 1082 records from Données LPO Réserve naturelle régionale du marais de la Vacherie. 15 records from Description of lithologic section units of IODP Hole 325-M0041A. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 226902 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 19619 records from Carabidae of the Carpathians. 23 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 857 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 25 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792 - 1851). 54531 records from NRW Regional Data: South East Wales Non-sensitive species. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 3 records from A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 591 records from Alan Wormington Collection. 105 records from Colección de Entomología del Museo de Historia Natural C.J. Marinkelle. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 7 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 510 records from University of Saskatchewan. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 17 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 5201 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 53415 records from Naturalis Biodiversity Center (NL) - Diptera. 8 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 1 records from A new Dysdera species (Araneae: Dysderidae) from Azerbaijan. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 74 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 1 records from Berlese's Primitive Oribatid Mites. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 159 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 7 records from Données du naturaliste Matthieu Gouirand. 47 records from The Stonefly Genus Lednia In North America (Plecoptera: Nemouridae). 1 records from Novel alpine algae from New Zealand: Chlorophyta. 5 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 93 records from New records of Crabronidae fauna (Hymenoptera, Apoidea) of Tunisia. 2 records from Taxonomic notes on the genus Hydrobaenus with description of H. simferopolus sp. nov. from Crimea (Diptera: Chironomidae). 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 13482 records from Insect specimens of Rikuzen-Takata City Museum. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 7 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 3 records from Wuhle - Brücke / B1. 31 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 46331 records from National Benthic Inventory. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 18 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 12 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 2 records from Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger B (Apidae, Colletinae). 14 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 53 records from DSMZ Bacteria. 278417 records from CAS Entomology (ENT). 70018 records from Carnet B Lorraine. 124 records from Naturalis Biodiversity Center (NL) - Pisces. 25 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 13410 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 44392 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 23 records from The Evaniidae (Hymenoptera: Evanioidea) of Turkey. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 57 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 23 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 49 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Three new species of the family Scathophagidae (Diptera) from the Palaearctic region with a redescription of the male of Amaurosoma longicorne. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 262 records from MoJ BioBlitz August 2018. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 46 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 3 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 14 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 17322 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 9640 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 172 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 27201 records from Marine benthic dataset (version 1) commissioned by UKOOA. 29876 records from European Moth Nights. 52 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 1259 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1450 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 104 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 4 records from MfN - Micropaleontology. 75 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 335 records from BUND - Dassower See (Lübeck/Dassow). 58754 records from Données naturalistes de Monsieur François FOURNIER. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 6 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 1 records from Sächsische Schweiz (Wehlener Gebiet). 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 16 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 222 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 133523 records from Hatikka Observation Database. 308 records from Données naturalistes de Monsieur JOURDE Rémi. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 115427 records from inatura - Erlebnis Naturschau Dornbirn. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 5 records from Benthic macrofauna abundance of sediment core 13078-015. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 21 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 70 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 3 records from Mycetocharina (Alleculopsis) bahukalatensis sp. nov. (Coleoptera: Tenebrionidae: Alleculinae) from Iran. 5 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 105506 records from Database of invertebrates collected in Mongolia. 84 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 32840 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 33 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 5 records from Three Oriental species of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae) from China. 4162 records from WTSWW Data: All Taxa (West Wales). 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 87 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 18 records from "Ahrschleife bei Altenahr". 164137 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 36 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 56 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 216 records from Ostracoda abundance of Hole 95-612. 107 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 17 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 44 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 4 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 20 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 23643 records from CNIN/Abejas de México/Apoidea. 21 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 2713 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 876 records from Ensemble des données Odonates. 2134 records from Kurzflügler_Raw1. 11 records from Notes on Catulona Rolston, 1992, and the description of a new species from Brazil (Hemiptera, Pentatomidae, Discocephalinae). 59 records from Seven new giant pill-millipede species and numerous new records of the genus Zoosphaerium from Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae). 6 records from Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 51 records from Revision of the spider genus Ischnocolus Ausserer, 1871 (Mygalomorphae: Theraphosidae: Ischnocolinae). 10 records from Ostracod species in Oligocene sediments of core CRP-3. 30 records from Thunberga gen. nov., a new genus of huntsman spiders from Madagascar (Araneae: Sparassidae: Heteropodinae). 50 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Nueva especie de Kessleria Nowicki, 1864 para Chile central (Lepidoptera: Yponomeutidae) asociada a Maytenus boaria Molina (Celastraceae). 627 records from BioBlitz Barcelona 2010-14. 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 6 records from Art´n Vielfalt im Kinderwald. 294 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 4 records from Benthic macrofauna abundance of sediment core 13077-093. 1 records from Invasive Non-Native Species, Outer Hebrides. 18 records from Phase 2 Lowland Grassland Survey of Wales. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 27 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 276498 records from hymenoptera. 378 records from FFH-Gebiet "Calwer Heckengäu". 119425 records from Naturalis Biodiversity Center (NL) - Crustacea. 12147 records from Danish Ants (Formicidae). 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 139 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 27 records from Partial revision of the genus Robinsonia Grote 1866: description of five new species for the Neotropical fauna (Lepidoptera, Erebidae, Arctiinae, Phaegopterina). 55 records from The Genus Daspletis Loew, 1858 And The Description Of Two New Genera, Anasillomos And Remotomyia (Diptera: Asilidae: Stenopogoninae). 1 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 81521 records from Bob Merritt Coleoptera Dataset. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 8 records from Component analysis of TV-guided grab sampler GeoB10071-5. 13768 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 7 records from Contribution to the Mesochorinae (Hymenoptera, Ichneumonidae) of Nepal. 228096 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 18982 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 649 records from Beetles from nature reserves and nearby forests in Østmarka. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 590 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3934 records from The Broward College Insect Collection. 28 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 11 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 12 records from Isoperla Umpqua A New Species Of Western Nearctic Stonefly (Plecoptera: Isoperlinae). 13 records from Eubria mesoamericana Barr and Shepard (Coleoptera: Psephenidae: Eubriinae), a New Psephenid Species from Central America with an Enigmatic Generic Distribution. 19 records from Distribution Data for Megachile chomskyi. 8 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 789 records from Occurrence of insect species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 93 records from South American Antarctic Marine Biodiversity Literature. 6 records from Description of Lacon mertliki sp. nov. (Coleoptera: Elateridae: Agrypninae) from the Hyrcanian forest ecoregion, with a key to the Lacon species of Iran. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 15 records from Université Pédagogique Nationale de Kinshasa- Les Insectes Comestibles de la R.D. Congo (Entomophagie). Projet CABIN (Central African Biodiversity Information Network). 33 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 9 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 31 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 78 records from SPC PROCFish/C Invertebrates Observations Papua New Guinea 2006. 14 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Ostracoda abundance of Hole 24-238. 252 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey. 5 records from Meiofauna abundance in sediment core 54301-010. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 41 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 3 records from Description of a new species of the genus Maua Distant (Hemiptera, Cicadidae) from China. 4 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 1 records from Pritchardia boliviensis N. Gen., N. Sp. (Anoplocephalidae: Linstowinae) a tapeworm from opossums (Didelphidae) in the yungas and lowlands of Bolivia and Atlantic forest of Paraguay. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 7 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 8987 records from NE Scotland other invertebrate records 1800-2010. 332 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 11791 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 16020 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 19 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 24 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 29 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 36 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 15 records from Ameroculodes miltoni, a new species of estuarine amphipod (Crustacea: Malacostraca: Peracarida: Oedicerotidae) from the southeastern United States. 249 records from Census of animals species through Benin from 2011 to 2019. 11 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 1063 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 70 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 12 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 16745 records from Données Entomologiques A. HORELLOU 1988-2018. 77 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 163 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 7 records from Тaxonomic position of Orthochirus olivaceus (Karsch, 1881), the type species of the genus Orthochirus Karsch, 1892 (Scorpiones: Buthidae). 12 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 1 records from Geführte Wanderung im Eselsbachtal. 6 records from A new species of Hygrogeus Mulsant & Rey, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from Xizang, China. 1536 records from Records of Halicarcinus planatus at sub-Antarctic regions. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 8 records from In the aftermath of Permian-Triassic boundary mass-extinction: new ostracod (Crustacea) genus and species from South Tibet. 31 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 281 records from EDIT - ATBI in Gemer area (Slovakia). 22137 records from Global compendium of Aedes albopictus occurrence. 2 records from Inventaire malacologique de la RNR des Marais de Stors. 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 10757 records from données aranéologiques de LEDOUX Jean-Claude. 31 records from Teich Berlin Wuhlheide. 56 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 7 records from AKG-Gelände (Bensheim). 40 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 27 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 10 records from Taxonomic and nomenclatural changes in three species of Pterostichus Bonelli (Coleoptera: Carabidae) from the Far East. 3 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 6 records from On the Chilopoda from Turkey. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 52 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 84 records from Ostracoda abundance of Hole 48-403. 3 records from Redescription of Deltamysis holmquistae Bowman & Orsi, 1992 (Crustacea Mysida: Mysidae), a mysid species new to the Atlantic Ocean with observations on the taxonomic status of Kochimysis Panampunnayil & Biju, 2007. 77 records from Shannon Index and species richness for arthropods. 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 1 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 148 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 15 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 39 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 4 records from Two new genera for the Botyodes species complex (Lepidoptera: Pyraloidea: Crambidae). 1497 records from Crustacea ZMK. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 1 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 23387 records from Liste des insectes associés au Vitellaria paradoxa C. E Gaertner, au Centre et au Nord du Bénin. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 283 records from Antarctic Amphipoda. 5 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 6 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 939 records from Coléoptères Silphidés du département du Loiret. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 12 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 1945 records from Modernisation des ZNIEFF du PnrL. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 179 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 33696 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 5344 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 112431 records from Tasmanian Museum and Art Gallery provider for OZCAM. 12 records from Pindamoraria boraceiae, a new genus and species of freshwater Canthocamptidae (Copepoda, Harpacticoida) from Brazil. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 97417 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 22 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 37 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 17202 records from Chrysomelidae beetle data from iRecord. 60 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 4 records from Faunal assemblage of sediment core TR149-32. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 40 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 4 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1664 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 7 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 94 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 7604 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 8 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 12 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 4774 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 14 records from MfN - Fossil vertebrates IV. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 69 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1969 records from Dipterists Forum: Field Week 1981 (Kent). 11 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1827 records from Eulachon migration bottom trawl surveys. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1833 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 81 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 17 records from Heavy minerals of sediment core PL94-64. 2099 records from Dolichopodidae of Portugal - dataset 2009-2018. 446 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 9 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 59 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2923 records from Données naturalistes d'Alain BERLY. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 183 records from (Table 6) Ostracod assemblages of sediment core 9409. 561 records from Données opportunistes. 2 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 1 records from Leeuwenia hollisi sp. n. (Thysanoptera, Phlaeothripinae) from New Guinea, with the tenth abdominal segment exceptionally long. 5 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 64 records from Inventaire et regroupement de données Natura 2000. 17 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 2 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 929 records from Species biodiversity transnational geo-database - IMPRECO Project. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Arthropoden aus südostalpinen Höhlen.. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1332 records from Données naturalistes de Loïc SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from Discovery of termitophilous tenebrionid beetles in China (Coleoptera: Tenebrionidae). 578 records from East Ayrshire Species Database. 100 records from Euroants. 45 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 60 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 31012 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 7 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 23 records from A Middle Devonian Trilobite Assemblage from Venezuela. 47 records from Three new species and six new records of Scathophagidae (Diptera) from Japan with a key to the Japanese genera. 9 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 8463 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 154 records from Dermaptera in the icipe collection. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 53 records from Schwanseepark (87645 Schwangau). 2 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 15 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 2957 records from Ecosphère_2017_12_18. 3 records from Cuccodorodes gen. nov., an apterous Batrisitae from the tropical Himalayas (Coleoptera: Staphylinidae: Pselaphinae). 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 16 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 11 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 3 records from Meiofauna abundance in sediment core 13368-015. 2 records from Caroperla brevihamata (Plecoptera: Perlidae), a new stonefly species from Guangxi Zhuang Autonomous Region of southern China. 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 36 records from schulgarten. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 6 records from Tauchen und Meer 02. 15 records from Review of Indotritia (Acari, Oribatida, Oribotritiidae) with a world checklist, a key to all known species, and a description of a new species from China. 3 records from Données naturalistes de THÉVENOT Jessica. 2 records from Trends of karyotype evolution in the Neotropical long-legged crickets Phalangopsidae (Orthoptera, Grylloidea). 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 817 records from Lucanidae. 81 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 13 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 267011 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 12 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 14 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2211 records from TWIC Biodiversity Field Trip Data (1995-present). 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 2 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 2 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 177 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 12 records from Myopa nebulosa sp. nov. and Myopa bozinovici sp. nov. (Diptera: Conopidae): New thick-headed flies from a threatened biodiversity hotspot in central Chile. 1 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 101 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 1 records from Genebank, National Institute of Agrobiological Sciences. 3 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from A new species of Bathynomus Milne Edwards, 1879 (Isopoda: Cirolanidae) from The Bahamas, Western Atlantic. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 24 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 13014 records from River Biologists' Database (EPA). 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 1 records from Description of a new genus and species of Hemisphaeriini from Brunei with an identification key to the Bornean species of the tribe (Hemiptera: Fulgoroidea: Issidae). 1 records from Great Eastern Ranges - Slopes to Summit. 97825 records from Tiroler Landesmuseum Ferdinandeum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 12 records from New or rare Madagascar tiger beetles- 20. Pogonostoma (Bathypogonum) horimichioi sp. nov. and supplemented characters of P. (B) levigatum levigatum (W. Horn) and P. (B.) levigatum lucens Rivalier (Coleoptera: Cicindelidae). 2373 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 5583 records from Données faune Nature 18 - 2017. 3 records from Hydaticus (Prodaticus) hauthi sp. nov., a new diving beetle from the cloud forest in the Cordillera El Sira, Peru (Coleoptera: Dytiscidae). 5 records from Benthic macrofauna abundance of sediment core 13077-063. 8851 records from Odonata records from RSPB Reserves 1970-2009. 24 records from Taxonomic revision of Australian Amobia Robineau-Desvoidy, 1830 (Sarcophagidae: Miltogramminae): integrating morphology and genetics finds a new species and tackles old problems. 18 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 7 records from (Table 4) New palynological record of sediments from Odderade. 3 records from Protist Diversity in the East China Sea. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 8 records from Données espèces - Expertise IPE 79. 351 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 1039363 records from NBIS Records to December 2016. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 172 records from Nezara viridula records held by the Royal Horticultural Society. 15 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 104 records from Rohrmeistereiplateau und angrenzendes Gebiet. 9 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 420 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1880 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 28 records from Some new species of Phaneroptera, Eulioptera and Scolocerca (Orthoptera Tettigoniidae: Phaneropterinae) from West Tropical Africa. 5 records from Four new species records of Antennoseius and Anystipalpus (Acari: Mesostigmata: Ascidae) phoretic on Carabidae beetles from France. 126 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 137578 records from Arizona State University Hasbrouck Insect Collection. 63364 records from CCAMLR historic KRILL. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 154 records from Chironomid remains in the sediment sequence of Site PG1212. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 2 records from A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data. 76969 records from MDFRC macroinvertebrate survey. 194 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 16 records from Amtsrain Apolda-Zottelstedt. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 13912 records from The national database for marine data (MADS). 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 23 records from The genus Arrhopalites (Collembola, Arrhopalitidae) in Asia, with the description of two new Japanese species of Yosiis collection. 8 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1098 records from What bug is that. 434 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 6 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 9 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 4 records from Warnowufer Groß Klein. 3 records from Paleotelmatoscopus, a proposed new genus for some fossil moth flies (Diptera Psychodidae, Psychodinae) in Eocene Baltic amber, with description of a new species. 9827 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 14 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1 records from A dryinid wasp in Early Eocene amber from the Paris basin (Hymenoptera: Dryinidae). 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 43993 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 4 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 54 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 2 records from Pygmodispus (Pygmodispus) paraequestris spec. nov. (Acari: Heterostigmata: Scutacaridae) from Turkmenistan. 6 records from Contribution to the knowledge of carabodid oribatid mites (Acari, Oribatida, Carabodidae) of Cuba. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1 records from Extracellular DNA marine sediment Targeted Locus (Loci). 18 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 3 records from A new species of Hemilea Loew and two new records of Trypetini (Diptera Tephritidae: Trypetinae) from India. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 26 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 210 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 3 records from Oratosquilla septemdentata n. sp. (Crustacea: Stomatopoda: Squillidae), a new species of deep water stomatopod from Halmahera, Indonesia. 6 records from Bachpatenschaft Beeke. 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 461 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from The endless search for type specimens; illustrations of eleven spider (Araneae Mygalomorphae) species described by Eugène Simon. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 59 records from Artenvielfalt auf den Elbwiesen (Dessau). 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 3 records from Taxonomic status of Cacoplox griseatus Hull, 1970 with redescription of the genus and type species (Diptera, Bombyliidae, Bombyliinae, Bombyliini). 474 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 5 records from Discovery of a new species of Trieces (Hymenoptera: Ichneumonidae: Metopiinae) questioning the traditional delimitation between Trieces and Chorinaeus. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 44553 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 12 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 4 records from Descriptions of Psychodidae (Diptera) from the Western Ghats of India. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 60 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 9 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 29173 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 1 records from On the Chilopoda from Turkey. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 3824 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 15182 records from Fife Nature Records Centre combined dataset. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 9 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 14 records from Naturschutzgebiet Lochbusch-Königswiesen. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 25 records from Review of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha Cicadellidae: Eurymelinae: Macropsini) of Southeastern Kazakhstan with description of new species. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 27 records from Review of Neocynorta Roewerı 1915 with two new generic synonymies (Opiliones: Gonyleptoidea: Cosmetidae). 7814 records from Odonata de Veracruz. 1 records from BIRDRACE Niederlausitz-Team. 171 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 622 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 712 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 42 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 4324 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 57 records from CG04_2017_12_18. 2 records from Charletonia Talebii N. Sp. From Iran (Acari, Prostigmata, Erythraeidae). 10 records from The Winter Stoneflies (Plecoptera: Capniidae) Of Mississippi. 89 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 126 records from Collection Ephemeroptera - SMF. 515 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 31 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 102438 records from Denver Museum of Nature & Science - Entomology. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 149 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19438 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 9846 records from Spider (NSMK-SP). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 1 records from Hoplophora ardua. 31 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 19 records from Schulgelände Lise Meitner Realschule (Paderborn). 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 88 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 7 records from Landwehrbach. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 67 records from CSIRO, fish surveys by the Soela, 1980s. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 10 records from Rajburicoris, a new genus of Cardiastethini, and discussion of the systematic position of Dufouriellus (Hemiptera: Heteroptera: Anthocoridae). 401 records from Données de VINCENT Alexis (SAPROX). 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 1171 records from Glasgow Museums BRC: Chrysomelidae. 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 2 records from A new species of Symbiopsocus Li (Psocodea: “ Psocoptera ”: Psocidae) from Taiwan, China, with a revised checklist and key to species. 27 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 43 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Myriatrix. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 2 records from Fossil Specimens of Komatsu City Museum. 37 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2318 records from Données naturalistes de Bernard Lalanne-Cassou. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 2 records from A new water mite species of the Hygrobates fluviatilis-complex from Russia (Acari Hydrachnidia, Hygrobatidae). 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 385 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 282 records from National Biodiversity Data Bank. Observation records, 1900-2014. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 10 records from A new species of Strouhaloniscellus Tabacaru, 1993 (Crustacea: Isopoda: Oniscidea) from a cave in Mt Biokovo, Croatia. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 13 records from Contribution to the knowledge of the Prioninae (Coleoptera, Cerambycidae) from the Mizoram State (India), with the first report of the genus Megobaralipton Lepesme & Breuning and new records from the country. 2 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12404 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 122848 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 2 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 23 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 27 records from Nottekanal, Klasse 7 - 10. 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 17073 records from données aranéologiques de CORNIC Jean-François. 45 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 4 records from Données espèces - Expertise IPE 69. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 14 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 26 records from Scorpiofauna of Kashan (Esfahan Province, Iran) (Arachnida: Scorpiones). 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 12 records from Révision du genre Paradorodocia Machatschke, 1957 (Insecta, Coleoptera, Rutelidae, Adoretinae). 2 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 7 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 62 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 1410 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 8 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 1 records from Description of Gondwanoscurus curleri sp. nov. from the West Usambara Mts, Tanzania (Diptera: Psychodidae). 88 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 2 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A New Ingolfiellid Amphipod Crustacean From Sandy Beaches Of The Gura Ici Islands, Western Halmahera (North Moluccas). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 209 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 5 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 9 records from Örtzemündung (Stedden). 2 records from Two new genera of Aradidae from Malaysia and Vietnam (Hemiptera: Heteroptera: Aradidae). 60221 records from National Stag Beetle Surveys (Great Stag Hunts). 51 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 11688 records from Marine Offshore Seabed Survey data held by JNCC. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 319 records from Données naturalistes de Monsieur LEFEBVRE François. 1211 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 11704 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 1004 records from Données odonates. 258 records from Malawi-Histeridae-Biodiversity-Data. 17318 records from Swiss National Diplopoda Databank. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 2 records from A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea Tetrigidae) from China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 6 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 7 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 3 records from Lednia Tetonica, A New Species Of Stonefly From Wyoming (Plecoptera: Nemouridae). 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 670 records from Benthos counted on dredged samples during Valdivia cruise VA53. 26 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 1049 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 7 records from Description Of A New Species Of Pterostichus Bonelli, P. barri, From The Appalachian Mountains (Coleoptera: Carabidae). 1933 records from Carabidae of the European North-East of Russia. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 1 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 106 records from A revision of the genus Paraleptognathia Kudinova-Pasternak, 1981 (Crustacea: Tanaidacea) and description of four new species. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 14 records from Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species. 7 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 1 records from Données naturalistes d'Anaïs MAS. 37 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9795 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 11 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 27 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 76 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 1 records from Sediment metagenome. 158008 records from BioFokus. 1254 records from Anymals+plants - Citizen Science Data. 8453 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1562 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 10 records from "Schwarzwassertal" bei Pobershau. 3 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 34509 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 519 records from Danielsberg (Mölltal, Kärnten). 75 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 7897 records from LPO_PACA_2017_12_18. 3 records from Oklahoma Vascular Plants Database Provider. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 656 records from Targeting a portion of central European spider diversity for permanent preservation. 630 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Liste des pays par taxon spécimen TOGO. 36 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 298 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 200 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 99 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 4979 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 179 records from Fossil (WSHN-FO). 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 17 records from Two new species of the genus Oryctopterus (Orthoptera: Stenopelmatidae: Oryctopinae) from India, with some notes on biology. 396 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 2 records from A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda Gebiidea: Laomediidae) from Japan. 9 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 17 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 72 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Biodiversidad de los Ecosistemas Mesofóticos de la Isla de San Andrés. 15433 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 375 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 59 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 28 records from WildesMoor bei Schwabstedt. 19 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 5924 records from ZooplanktonBeaufortSeaNOGAP2. 25 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 389 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 4 records from New species of Langona Simon, 1901 and Neaetha Simon, 1884 (Araneae Salticidae) from Thailand. 1 records from DAR AVH data. 35651 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 1 records from A new species of Proneuronema (Neuroptera: Hemerobiidae) from late Eocene Rovno amber. 17 records from New records of Reduviidae (Hemiptera: Heteroptera) from Argentina. 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 1 records from DBL_Life. 4 records from Multiple original spellings, living authors and the Code: The case of Malachius raniansis Mawlood, Hammamurad & Abdulla, 2017 (Coleoptera: Melyridae). 150 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 10 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 45 records from Gronau - auf der Suche nach dem Neunauge. 78 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 19535 records from Eden Arthropod Azores Database. 8 records from Two new species of Nyctelia Latreille (Coleoptera: Tenebrionidae) from Argentinean Patagonia with zoogeographical and ecological remarks. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 5 records from Faunal assemblage of sediment core GS7603-8. 60 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2171 records from Thrips (Thysanoptera) in Norway. 16 records from Entdeckertour am Muldestausee 1/05. 1442 records from Abundance and distribution of coastal, inshore zooplankton in the Huon Estuary and D'Entrecasteaux Channel, Tasmania, Australia (2004-2005). 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 29 records from BIOTOPE_2017_12_18. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 8 records from New and little-known crickets from Southern Guangxi, China (Orthoptera: Grylloidea: Gryllidae: Phalangopsidae; Trigonidiidae). 1421 records from Weevils of Poland. 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 36 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1764 records from Arachnida of Costa Rica (INBio). 11 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 53 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 3076 records from Ross A. Layberry, Collection. 3 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 5 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 33 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 3 records from Niuailan, a new genus to accommodate Carneoryctes peterseni (Endrődi, 1967) (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from New Ireland, Papua New Guinea. 3 records from A remarkable example of symbiosis between an animal and a fungus in a new species of legless mealybug (Insecta: Pseudococcidae). 461 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 6 records from Melphidippidae *. 32 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 419 records from Galathea II, Danish Deep Sea Expedition 1950-52. 15 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 12299 records from NCSM Non-molluscan Invertebrates Collection. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 5 records from A new Palnia STEBNICKA, 1985 species from Oriental region (Coleoptera, Scarabaeidae, Aulonocneminae). 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 2 records from Newly reported genus Batracomorphus Lewis (Hemiptera: Cicadellidae: Iassinae) from Pakistan with description of a new species. 6 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 1345 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 7967 records from Colecção Entomológica do Museu de História Natural de Maputo. 1 records from A new species of Umanella Gauld (Hymenoptera, Ichneumonidae) from Ecuador. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 32 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 31 records from Craigellachie NNR invertebrate records compiled from SNH files. 1 records from Collection Polychaeta - ZSRO. 16486 records from imr_mareano_rpsledge. 137 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 1037 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 44 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 40 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 100 records from Données d'observation d'écrevisses exotiques envahissantes en Haut de France et Normandie sur la période 2014 à 2018. 2 records from Abundance of benthos infauna at station GIK23055-1. 2 records from Description of a new whiteflyı Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ı infesting Quercus leucotrichophora (Fagaceae) in the Western Himalayaı India. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Brazil. 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 485667 records from Swiss National Grasshoppers Databank. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 22761 records from Weevil and Bark Beetle records via iRecord. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 113 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 5 records from Nationalpark Harz Schul-AG Braunlage. 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 8 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 11 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 629 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 19 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 440 records from Wichita State University Collection. 68 records from Données naturalistes de Pierre-Alexis RAULT. 225 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 402 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 5 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 21 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 638 records from pbzt_insect_biodiversity. 15 records from NZCS Upper Tapanahony Expedition 1991. 9 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 34 records from A taxonomic revision of Otomantis Bolivar, 1890 (Mantodea: Hymenopodidae, Acromantinae) with description of five new species. 1 records from Oppia nitens. 7 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 42 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 91 records from Fossil (NSMK-FO). 6 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 2 record
Keywords: GBIF; biodiversity; species occurrences